Anthropology and Biblical Studies : Avenues of Approach - Lawrence, Louise J., (Deo Publishing, Religion and Theology Special E-Book Collection, 1999-2017, ISBN: 9789004401549., 2004)
Presents the findings of an international research symposium, held at St Andrews University, Scotland, in July 2003. Contributors include both biblical scholars and anthropologists. The essays presented variously explore and review interdisciplinary links, innovations and developments between anthropology and biblical studies in reference to interpretation of both the OT and NT and pseudepigraphal works. Explored are methodological issues, the use of anthropological concepts in biblical studies (identity; purity boundaries; virtuoso religion; spiritual experience; sacred space) and more 'field orientated' work of bible translators in different cultures.